Dhāndhalāṃ rī khyāta - Rāṭhauṛa, Vikramasiṃha; Rajasthani Shodh Sansthan (Jodhapura : Rājasthānī Śodha Saṃsthāna, 2006)
History of the Dhāndhalāṃ branch of the Rashtrakutas, dynasty of Jodhpur, Princely State; covers the period 13th to 17th century; includes text of the manuscript.
"Rājasthānī Śodha Saṃsthāna Svarṇa Jayantī varsha ke upalakshya meṃ prakāśita"--T.p. verso.
Mode of access: Internet.
In Rajasthani.
Keywords: Rashtrakutas -- Sources; Jodhpur (Princely State) -- History -- Sources